Quantitative variation in the core bacterial community associated with honey bees from Varroa-infested colonies. Issue 3 (27th May 2019) - Marche, Maria Giovanna; Satta, Alberto; Floris, Ignazio; Pusceddu, Michelina; Buffa, Franco; Ruiu, Luca
Abstract : Infestations of the ectoparasitic mite Varroa destructor cause significant honey bee colony weakening, due to both host-feeding and virus transmission effects. In addition to the natural (i.e., behavioral) and innate (i.e., cellular and humoral response) mechanisms of defense against pathogens and parasites, contribution to maintain good colony health may derive from the resident microbial community. The present study investigated variation in immune-related gene expression levels and in the relative abundance of representative bacterial taxa of the core honey bee microbiota in colonies infested by Varroa mites in comparison with honey bees from non-infested colonies. Significant changes in the target bacterial taxa (Gammaproteobacteria, Betaproteobacteria, Lactobacillus spp., Bifidobacterium spp., Brevibacillus laterosporus ) were detected in immune-suppressed adults emerging from Varroa -infested colonies. Insect stages randomly sampled from infested and non-infested hives were characterized by high variability. Emerging adults bearing sucking Varroa mites on their body showed a considerably higher deformed wing virus titer and a greater immune gene downregulation compared with adults without mites. Further, the abundance of the overall bacterial community and of specific bacterial taxa increased significantly in parasitized adults. A possible compensation mechanism involving the core bacterial community in Varroa -infested hives is discussed.